IMPLEMENTASI METODE KETELADANAN GURU DALAM MENINGKATKAN AKHLAK PESERTA DIDIK DI MADRASAH ALIYAH AL-MUNAWAROH DIWEK JOMBANG - Riski Rahmawati; Shobihus Surur (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
This study discusses the Implementation of the Teacher Exemplary Method in Improving Student Morals at Madrasah Aliyah Al-Munawaroh Diwek Jombang. The exemplary method is one of the most influential strategies for students in the teaching and learning process considering that every human being has the nature to imitate (imitate) every behavior, speech, and dress. The exemplary method (uswah hasanah) in the perspective of Islamic education is the most convincing influential method for the successful formation of moral, spiritual and social ethos aspects of students. The lack of role models from educators in practicing Islamic values is one of the factors causing the moral crisis. The purpose of this study is to find out the implementation of the teacher exemplary method in improving the morals of students. This study uses a phenomenological approach with qualitative research methods. The results of this research show that: teacher example is very important in improving students' morals, morals are an important part of education. By having good morals, it is hoped that students can differentiate between good and bad. The exemplary method is a method that is considered very effective in efforts to improve student morals. A teacher who consistently applies moral and ethical values ​​in daily behavior can have a positive impact on student attitudes and behavior